2022
DOI: 10.1029/2022jb024638
|View full text |Cite
|
Sign up to set email alerts
|

A Common Diffusional Mechanism for Creep and Grain Growth in Polymineralic Rocks: Experiments

Abstract: We conducted uniaxial compression and grain growth experiments on fine‐grained forsterite (Mg2SiO4) + 10 vol% periclase (MgO) aggregates. This aggregate is a unique polymineralic system in which all of the constituent elements in the secondary phase constitute the primary mineral phase, except for Si, which is the slowest diffusing species in the primary phase. Grain growth in polymineralic aggregates, where the presence of a secondary phase results in grain boundary pinning of the primary phase, proceeds via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…In previous work from our laboratory, we have conducted 1-atm high-temperature creep tests on fine-grained olivine aggregates at small stress, where dislocation processes would be suppressed (Maruyama & Hiraga, 2017a;Miyazaki et al, 2013;Okamoto & Hiraga, 2022;, and found different mechanical and microstructural characteristics from what we have believed for a long time. One is power-law creep identified at lower stresses and smaller grain sizes than the conditions at which grain-boundary diffusion creep dominates .…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In previous work from our laboratory, we have conducted 1-atm high-temperature creep tests on fine-grained olivine aggregates at small stress, where dislocation processes would be suppressed (Maruyama & Hiraga, 2017a;Miyazaki et al, 2013;Okamoto & Hiraga, 2022;, and found different mechanical and microstructural characteristics from what we have believed for a long time. One is power-law creep identified at lower stresses and smaller grain sizes than the conditions at which grain-boundary diffusion creep dominates .…”
mentioning
confidence: 78%
“…This situation complicates the determination of the actual Al 2 O 3 activity of anorthite during the deformation tests. Okamoto and Hiraga (2022) recently showed that grain-boundary diffusion processes for creep and grain growth in olivine are strongly sensitive to MgO activity. However, the present study could not clarify such activity effect on the creep properties of anorthite.…”
Section: Al/si Ratiomentioning
confidence: 99%
“…Specifically, Ol single crystals buffered by Per are stronger than those buffered by Opx in the dislocation creep regime (Bai et al., 1991; Ricoult & Kohlstedt, 1985). Additionally, in the diffusion creep regime, polycrystalline samples of Fo 100 + 10% Per 100 (Okamoto & Hiraga, 2022) are approximately an order of magnitude stronger than samples of Fo 100 + 20% En 100 (Nakakoji et al., 2018). To test the effect of silica activity on the strength of our samples deforming in the dislocation‐accommodated grain‐boundary sliding creep (disGBS) regime, an additional experiment was conducted on a sample of Ol + <10% Per 70 that yielded a strength within error of, if not slightly weaker than, that predicted by the disGBS flow law determined by Hansen et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we discuss feasible grain growth and diffusion creep processes in the lower mantle, drawing insights from our previous work, especially regarding grain growth and creep of forsterite + enstatite (Nakakoji & Hiraga, 2018; Nakakoji et al., 2018) and forsterite + periclase (Okamoto & Hiraga, 2022).…”
Section: Grain Growth and Creep Of The Lower Mantle Materialsmentioning
confidence: 99%
“…Interestingly, a similar deviation has been identified for grain growth. Using the classical grain growth model for a polyphase system (Ardell, 1972a), δDGB_gr ${\delta D}_{\text{GB}\_\text{gr}}$ has been found to be systematically larger by a factor of 9 compared to the values predicted based on δDSi_GB ${\delta D}_{\text{Si}\_\text{GB}}$ (Nakakoji & Hiraga, 2018; Okamoto & Hiraga, 2022). Our proposition that grain growth can be viewed as part of the primary phase creep process led us to infer that this deviation is also due to a contribution from GBS during grain growth, which is not considered in the classical grain growth model.…”
Section: Grain Growth and Creep Of The Lower Mantle Materialsmentioning
confidence: 99%